The Use of Make a Match Technique in Teaching How to Communicate About Greeting in Student Class X MIA 3 SMA Negeri 1 Sigli Academic Year 2021/2022 - Farizawati Farizawati; Mariati Mariati; Ramlan Ramlan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is entitled “The Use of Make a Match Technique in Teaching How to Commicate about Greeting in Student Class X MIA 3 SMA Negeri 1 Sigli in the Academic Year 2021/2022.” The expected goal is to improve English speaking skills in greeting. The problem behind this research is the lack of student interest in learning to speak. To overcome this, it takes effort and creativity of teachers. The use of card media with several forms of greeting is one of the efforts to solve this problem. The data analysis technique used descriptive analysis. The results showed that 75% achieved complete learning and as many as 89.7% of students actively participated in learning. With the use of the card media, it can improve the results of learning English in the speaking skills aspect of class X MIA 3 students of SMA Negeri 1 Sigli. In addition, the use of card media can increase student motivation and activity in the learning process so that learning outcomes also increase.